Changes in the Damping Ratio and Energy Transfer Ratio Due to Damage in a Composite Beam - Jarosińska, Małgorzata (Engineering Transactions, 2026)
This paper investigates changes in the modal parameters of a composite beam resulting from damage introduced to the bottom flange of a steel I-beam. Variations in the modal damping ratio and energy transfer ratio (ETR) are analysed. The results of experimental tests and numerical analyses are presented. The beam was modelled using the rigid finite elements (RFEs) method. The introduced damage caused small changes in the damping ratio. In contrast, the ETR was found to be more sensitive to damage than the damping ratio in the experimental results, exhibiting variations on the order of several tens of percent. In the numerical simulation results, changes in the ETR were smaller, reaching a few percent.